Why do the ithomiines (Lepidoptera, Nymphalidae) aggregate? Notes on a butterfly pocket in central Brazil - Pinheiro,Carlos E. G. (2008)
This study provides information on the species composition and the number of butterflies in different phases of an ithomiine aggregation during the 2004 dry season in central Brazil, and tests some hypotheses concerning the pocket formation. The results obtained suggest that ithomiine pockets constitute primarily an adaptation of butterflies to the adverse climatic conditions of the dry season, such as high temperatures and low air relative humidity, rather than the occurrence of large concentrations of adult food resources (flowers visited for nectar were not found in the pocket site) or defense against visually hunting predators (contrary to the prediction tested, the frequency of butterflies bearing birds beak marks on the wings significantly increased along the period of pocket formation, especially in the case of Mechanitis polymnia, the most abundant species in the pocket). Other hypotheses concerning the pocket formation are also discussed.